Ecologically Safe Directions of the Low Rank Coal Bioconversion - Chernysh Y.; Plyatsuk L.; Ablieieva I.; Yakhnenko E.; Roubik H.; Miakaieva H.; Bataltsev E.; Danilov D. (Журнал інженерних наук)
This paper deals with theoretical research of the biochemical features of low rank coals (LRC) treatment. The biochemical bases of the organic component degradation of LRC and the biochemical principles of bioleaching of sulfur compounds and metals from LRC are presented. The analysis of microorganisms’ groups was carried out and the optimal conditions of their cultivation were determined. Electronic databases such as KEGG, BacDive, and EAWAG-BBD were used to identify the necessary ecological and trophic groups of microorganisms and to realize the patterns of trophic interactions in associations of different groups of microorganisms both under anaerobic and aerobic conditions. The methodological approach was applied and principle diagram of biochemical research of LRC processing was formed in order to develop the environmentally friendly direction of biogas and humic products production.